1997
DOI: 10.1001/jama.1997.03540440058033
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Oral Potassium on Blood Pressure

Abstract: Our results support the premise that low potassium intake may play an important role in the genesis of high blood pressure. Increased potassium intake should be considered as a recommendation for prevention and treatment of hypertension, especially in those who are unable to reduce their intake of sodium.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
154
2

Year Published

1999
1999
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 813 publications
(167 citation statements)
references
References 71 publications
11
154
2
Order By: Relevance
“…A recent meta-analysis, however, reported that an increased potassium intake had no statistically significant effect on BP [28]. And yet, other meta-analyses reported that an increased potassium intake lowered BP in patients both with and without hypertension [8, 29-30]. A WHO-sponsored study [31] showed an added complexity of the relationship between potassium and BP, as it found that potassium intake was negatively associated with both SBP and DBP in Tibetan participants but was positively associated with SBP and DBP in Han participants (Han is the majority ethnicity in China).…”
Section: Discussionmentioning
confidence: 99%
“…A recent meta-analysis, however, reported that an increased potassium intake had no statistically significant effect on BP [28]. And yet, other meta-analyses reported that an increased potassium intake lowered BP in patients both with and without hypertension [8, 29-30]. A WHO-sponsored study [31] showed an added complexity of the relationship between potassium and BP, as it found that potassium intake was negatively associated with both SBP and DBP in Tibetan participants but was positively associated with SBP and DBP in Han participants (Han is the majority ethnicity in China).…”
Section: Discussionmentioning
confidence: 99%
“…Observational epidemiologic studies have reported an inverse association between dietary potassium intake and BP [8,18,27]. Clinical trials have documented that potassium supplementation reduced BP in both hypertensive and normotensive subjects [8,18].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials have documented that potassium supplementation reduced BP in both hypertensive and normotensive subjects [8,18]. The BP-lowering effect of potassium supplementation might vary among individuals.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations